DEVELOPING MATHEMATICS LEARNING KITS IN STATISTICS COMPETENCY BY PROBLEM BASED LEARNING APPROACH IN TERMS OF MATHEMATICS LEARNING ACHIEVEMENT FOR JUNIOR HIGH SCHOOL STUDENTS - Wulandari .; Heri Retnawati (Jurnal Pedagogi Matematika, 2017)
This  study  aimed to develop mathematics  learning  kits  such  as  lesson  plan  and  student worksheet  by  Problem  Based  learning  approach  in  statistics  competency  for  junior  high  school student  grade  VII, and to  know  the  quality  of  learning  kits  based  on  validity,  practicality,  and effectivity aspects. This study was a developing research address to ADDIE developing model, those are  Analysis,  Design,  Development,  Implementation,  and  Evaluation.The  quality  of  learning  kits validity reached valid criteria, showed by mean of lesson plan validity was 4.11 from maximum score 5 with good qualification (x 4,2)and mean of student worksheet validity was 4.01 from maximum score  5  with good  qualification (x    4,2).The  quality of  learning  kits  practicalityreached  practicalcriteria, showed by mean of student response questionnaire was 3 from maximum score 4 with good qualification(2,8̅≤3,4), teacher  response  questionnairewas  3.01  from  maximum  score  4  with good  qualification (2,8̅≤3,4), and observation  result  of  learning  activity was  95%  with  very good category. Beside that, the quality of learning kits saw from effecticity aspect reached effective criteria.  It  showed by  mean  of  student  study  result test  was  93.5  and  its  percentage  of  students graduationwas 100%. Keywords: learning kits, Problem Based Learning, statistics competency, student achievement.